PEMBERDAYAAN MASYARAKAT MELALUI KEGIATAN PENGOLAHAN BIJI KOPI SIAP PAKAI PADA MASYARAKAT DESA GAMBIRI NAGORI SILABAH JAYA KABUPATEN SIMALUNGUN 2025 - Abryan Termedia Panjaitan; Rio Evrist Situmorang; Aldi G P Manurung; Niko A Hutabarat; Azarya N J Siahaan (Abdi Jurnal Publikasi, 2025)
Gambiri Village, Nagori Silabah Jaya, Dolok Paradamean District, Simalungun Regency, is a mountainous and hilly area, including a highland area with an altitude of 800-1225 meters above sea level. In this village, the greatest agricultural potential is coffee plants which are the mainstay of the economy in Nagori Silabah Jaya. Based on the results of the field assessment regarding the condition of the community regarding the availability of environmental conservation activities, it can be seen that the community does not yet have an awareness of the importance of environmental conservation based on the results of community economic activities so that there is continuity between community economic activities and environmental conservation. In this case, the potential for controlling environmental stability can be examined from the condition of the majority of residents' livelihoods which are dominated by Coffee Farmers. Partners are unable to market their coffee optimally, one of the obstacles felt by partners is inadequate product packaging. In addition, partners also want to be able to process coffee beans into ready-to-drink coffee with good quality. Therefore, it can be seen that it is necessary to hold a Community Service program through the Coffee Farmer Empowerment Training activity through Capacity Building in Coffee Processing in Gambiri Village, Nagori Silabah Jaya, Simalungun Regency.